THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN BUILDING A TOLERANCE ATTITUDE AMONG ADOLESCENTS IN THE ERA OF GLOBALIZATION - Ali Samsi; Moh. Jasri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to explore the role of Islamic Religious Education in fostering tolerance among adolescents in the era of globalization, focusing on a case study at SMP Negeri 6 Situbondo. Amid increasing social diversity and potential conflicts, cultivating tolerance is crucial for creating social harmony. Employing a qualitative approach, data were collected through observations, interviews, and document analysis. The findings indicate that Islamic Religious Education significantly contributes to the development of tolerant attitudes by teaching values of moderation and respect for diversity. Interactive learning methods and interfaith social activities within the school further enhance students' tolerance. This research concludes that religious education serves as a vital foundation for shaping tolerant and adaptable character in youth facing global challenges. The study's implications suggest the need for curriculum development that emphasizes moderation and interreligious dialogue.